Latent Class Analysis of Peer Conformity: Who Is Yielding to Pressure and Why?. (December 2013) - Kosten, Paul A.; Scheier, Lawrence M.; Grenard, Jerry L.
This study used latent class analysis to examine typologies of peer conformity in a community sample of middle school students. Students responded to 31 items assessing diverse facets of conformity dispositions. The most parsimonious model produced three qualitatively distinct classes that differed on the basis of conformity to recreational activities, deviant behaviors, style conformity, and social comparison. Gender comparisons suggested relatively stable class proportions for males and females but also significant parameter differences in tests of measurement invariance for latent class indicators. Multinomial logistic regression models predicting class membership from auxiliary covariates and psychosocial risk indicated that compared to mild conformists deviance conforming youth were more likely to be White, have low self-esteem, refrain from using adaptive coping skills, and be more socially anxious. Socially conforming youth were more likely to be male, White, and have low self-esteem. Findings are discussed with regard to classic definitions of conformity and its role as a developmental phenomenon.